Evidências de validade do Millon Behavioral Medicine Diagnostic (MBMD) na avaliação psicológica de candidatos à cirurgia bariátrica - Lucena, Marianna Carla Maia Dantas de (2013)
the Millon Behavioral Medicine Diagnostic is an instrument, developed from a consensus among health professionals, to identify psychological factors that may compromise the conducting of medical treatment in order to allow a better adhesion. As it has been one of the most used tools to assess bariatric surgery, the objective of this research is to verify the evidence validity of Millon Behavioral Medicine Diagnostic (MBMD) for psychological assessment of candidates for bariatric surgery. Method: males and females volunteers, aged 18 to 70, grouped in 150 patients admitted for surgical procedures or suffering from chronic diseases (control group) and 426 patients candidates for bariatric surgery, contacted in person or by the internet. For the study in the face group were also administered Millon Index of Personality Styles (MIPS), the Millon Clinical Multiaxial Inventory-III (MCMI-III) and the General Health Questionnaire of Goldberg, just in bariatric surgery patients. Results: there are indicators of semantic adaptation of the instrument, with 27 factors in five areas of the instrument, all with satisfactory levels of validity. The reliabitity indicators were satisfactory in 18 of the 32 scales that comprise the MBMD, while relations with the other three instruments showed significant variations compared to the original indicators. The MBMD was sensitive to differences between groups about gender, age, education, marital status, body mass index, comorbidities and chronic disease patients and with or without obesity. The use of this instrument in the assessment of candidates for bariatric surgery presents indicators of validity in view the limitations as to the realiability of certain scales